Metode Trend Moment untuk Prediksi Data Trend Naik - Brata, Adika Setia; Ramadhani, Ramadhani; Lestari, Windy; Rahmawati, Suci (SAINTIFIK, 2025)
Non-oil and gas exports are exports carried out outside the gas and oil sectors. Some examples of Indonesia's non-oil and gas export commodities are: Coffee beans, Tea, Spices, Tobacco, Cocoa beans, Shrimp, Textiles, Processed wood products, Palm oil, Chemicals, and others. Export activities are one component of aggregate expenditure because exports can affect the level of national income to be achieved. If exports increase, aggregate expenditure will increase and will then stimulate a country's economic growth. This value can be predicted using the trend moment method which is developed for upward trend data patterns. The stages of this method explain the problem of predicting the Value of Non-Oil and Gas Exports in 2023-2024 using the trend moment method. This method is carried out by looking at the trend line in past data and then applying mathematical principles to the stages of the calculation processes. The test results show that the accuracy of the trend moment prediction model in the 2023-2024 Non-Oil and Gas Export Value data is classified as good with a good Mean absolute percentage Error (MAPE) calculation percentage.